Percutaneous Coronary Intervention with Stenting versus Coronary Artery Bypass Grafting in Stable Coronary Artery Disease - Glenn, Ian C.; Iacona, Gabriele M.; Mangi, Abeel A. (International Journal of Angiology, 2021)
The debate over coronary artery bypass grafting (CABG) or percutaneous coronary intervention (PCI) with stent placement for the treatment of stable multivessel coronary artery disease (CAD) continues in spite of numerous studies investigating the issue. This paper reviews the most recent randomized control trials (RCT) and meta-analyses of pooled RCT data to help address this issue. General trends demonstrated that CABG was superior in all-cause mortality and fulfilling the need for repeat revascularization. These advantages tended to be more pronounced in multivessel CAD and diabetes, and less so in left main CAD. PCI showed a consistently lower rate of cerebrovascular events. CABG continues to offer significant advantages over PCI, even as drug-eluting stent technology continues to evolve. The ideal endpoint for comparing PCI and CABG remains to be determined. Furthermore, additional research is required to further refine patient selection criteria for each intervention.
Keywords: coronary artery; PCI; stent; cardiac surgery; cardiac catheterization; cardiovascular disease; myocardial infarction